Characterization of the NRAMP1 (SLC11A1) gene in the horse (Equus caballus L.) - Matiasovic, J; Kubícková, S; Musilová, P; Rubes, J; Horín, P (European journal of immunogenetics, 2002)
The complete coding cDNA sequence of the horse NRAMP1 (SLC11A1) gene was determined (GenBank accession number AF354445). The nucleotide sequence of the horse NRAMP1 gene is similar to sequences of this gene in other species. The gene contains 15 exons whose total length of 1,635 bp corresponds to 544 amino acids constituting the resulting putative protein. Hydrophobicity profile analysis of the deduced horse NRAMP1 gene product showed a nearly identical structure with the mouse NRAMP1 protein. The gene was found to be located on the short arm of ECA 6p12-13 by fluorescence in situ hybridization (FISH) analysis. Five allelic variants of the 5' untranslated region (UTR) were identified at the nucleotide sequence level. PCR-RFLP polymorphisms for NlaIII, TaqI, MspI and AciI were detected. Four out of five alleles could be detected using TaqI and MspI restriction enzymes. Their haplotype frequencies were different in four genetically distinct horse breeds.
Keywords: hydrofobní a hydrofilní interakce; Molecular Sequence Data; Sequence Analysis, DNA; sekvence aminokyselin; 5' nepřekládaná oblast; polymerázová řetězová reakce; Polymerase Chain Reaction; polymorfismus délky restrikčních fragmentů; Cation Transport Proteins; Horses; 5' Untranslated Regions; Physical Chromosome Mapping; Base Sequence; sekvence nukleotidů; Hydrophobic and Hydrophilic Interactions; zvířata; Amino Acid Sequence; koně; Polymorphism, Restriction Fragment Length; sekvenční analýza DNA; proteiny přenášející kationty; molekulární sekvence - údaje; fyzikální mapování chromozomů; Animals